2012
DOI: 10.1371/journal.pone.0043539
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Persistency of Resting and Active Periods of Locomotor Activity in Schizophrenia

Abstract: Patients with schizophrenia frequently exhibit behavioral abnormalities associated with its pathological symptoms. Therefore, a quantitative evaluation of behavioral dynamics could contribute to objective diagnoses of schizophrenia. However, such an approach has not been fully established because of the absence of quantitative biobehavioral measures. Recently, we studied the dynamical properties of locomotor activity, specifically how resting and active periods are interwoven in daily life. We discovered unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 41 publications
8
65
2
Order By: Relevance
“…This association between negative symptomatology and AL has been reported repeatedly in previous studies [3,6,14,15,16]. However, these studies failed to take the multidimensionality of the negative syndrome into account.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This association between negative symptomatology and AL has been reported repeatedly in previous studies [3,6,14,15,16]. However, these studies failed to take the multidimensionality of the negative syndrome into account.…”
Section: Discussionsupporting
confidence: 72%
“…Although associations between negative symptoms and AL have been reported rather consistently [3,6,14,15,16], Walther et al [14] failed to find an association between AL and the motor items of the Positive and Negative Syndrome Scale (PANSS), i.e. excitement, motor retardation and disturbance of volition.…”
Section: Introductionmentioning
confidence: 99%
“…5 Indeed, locomotor hyperactivity has widely been used to model positive symptoms of schizophrenia in rodents because of its association with hyperdopaminergic states. 37 Our findings and those of Sano and colleagues 27 call for the exploration of temporal patterns of animal motor behavior, which might become an interesting model for positive symptoms in schizophrenia. For larger scale rest-activity patterns, this has been already attempted.…”
Section: Implications For Translational Researchmentioning
confidence: 68%
“…The authors reported less variable behavioral movement patterns in schizophrenia patients. 27 This study did not find associations of behavioral patterns with psychopathology, probably due to the small sample size and the inclusion of data collected during sleep. In our study, the pattern of locomotor behavior in 100 schizophrenia spectrum patients was analyzed in 2 60-min periods at very small time scales, ie 2-s intervals.…”
Section: Patterns Of Motor Behaviormentioning
confidence: 72%
See 1 more Smart Citation